KARAKTER DAN KERAGAMAN JENIS POHON SARANG ORANGUTAN SUMATERA (Pongo abelii) DI STASIUN RISET SUAQ BELIMBING TAMAN NASIONAL GUNUNG LEUSER - Lailan, Infitar; Ruskhanidar, Ruskhanidar; Rahmi, Erdian (Jurnal Nusa Sylva, 2022)
The Sumatran orangutan (Pongo abelii) is an arboreal primate that spends all its daily activities in the trees. Nest-making activities are carried out daily, selecting trees with certain characteristics to make nests. Much research has been done on the character of orangutan nest trees. However, there needs to be more information about the character of orangutan nest trees at the Suaq Belimbing Research Institute, Gunung Leuser National Park. It is known that Suaq Belimbing is a peat swamp forest ecosystem in Gunung Leuser National Park, precisely in Kluet, South Aceh, with quite diverse vegetation composition. Even so, not all vegetation is used as orangutan nest trees. This study aims to obtain data on the characteristics of orangutan nest trees in the Suaq Belimbing peat swamp forest habitat of Gunung Leuser National Park. Data was collected for three months using the line transect method. The results of the study obtained 65 individual trees used as orangutan nests. 45.15% of the nest tree characters had a height of 11-20 m, and 24.46% had a trunk diameter of 31-40 cm. The most widely used crown shape for making nests was cylindrical.